7P’s marketing strategy affecting customer purchase intention towards a house in Arataz Equity Sdn.Bhd / Nik Dalila Nik Aziz - Nik Aziz, Nik Dalila (Faculty of Business and Management, 2009)
To be successful, organizations must look into the needs and wants of their customers. This is the reason why many researchers have continuously emphasized on the importance of 7P’s marketing strategy. This will be a result for customer satisfaction is really important because many researchers have shown that customer satisfaction have positive effect on an organization. Due to this, an organization especially ARATAZ EQUITY SDN.BHD must really understand what is exactly 7P’s marketing strategy affecting customer purchase intention towards a house in ARATAZ EQUITY SDN.BHD. There are variety of customer intention and looking before they proceed to the next stage such as product, place, price, promotion, process, people and physical evidence that ARATAZ EQUITY SDN. BHD offered. besides, the feedback from the questionnaire that the researcher distributed also gives an impact to the company. All this feedback can upgrade the performance of the company, Therefore, if an organization really understand what exactly the customer or potential buyer really needs and all these 7P’s tally with it, it is not impossible for the company to satisfy them as well as to gain much profit.